A Randomized Controlled Clinical Trial to Assess the Efficacy of Paya Sharkara Seka in Shushkakshipaka Special Reference to Dry Eye Syndrome - Rosh, Athira; Nair, Praveena P (Journal of Neonatal Surgery, 2025)
Background: Shushkakshipaka, correlated with Dry Eye Syndrome, is a prevalent ocular surface disorder characterized by tear film instability, foreign body sensation, and ocular discomfort. Conventional therapy often yields transient relief. Objective: To evaluate the clinical efficacy of Yashtimadhu Ksheerapaka Seka compared to artificial tear drops in managing Shushkakshipaka (Dry Eye) based on subjective and objective parameters. Methodology: A randomized controlled clinical trial was conducted on 30 subjects diagnosed with Shushkakshipaka, divided into Group A (Yashtimadhu Ksheerapaka Seka) and Group B (artificial tear drops). Treatment was administered for 10 days with follow-up on day 21. Assessment included subjective symptom grading and objective tests—Schirmer’s Test and Tear Film Break-Up Time (TBUT). Data were statistically analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. Results: Group A showed highly significant improvement in symptoms: Rooksha (Z = -3.49, p < 0.001), Gharsha (Z = -3.62, p < 0.001), Toda (Z = -2.97, p < 0.01), and Daha (Z = -3.28, p < 0.01), compared to Group B. Objective scores also improved significantly in Group A: Schirmer’s Test (Z = -3.69, p < 0.001; AF score: 2.6 ± 0.50) and TBUT (Z = -3.69, p < 0.001; AF score: 2.3 ± 0.44). Group B showed lower efficacy in both subjective (Rooksha: 1.7 ± 0.62; Gharsha: 1.5 ± 0.54) and objective outcomes (Schirmer’s: 2.0 ± 0.55; TBUT: 1.8 ± 0.47). Overall, Group A demonstrated better therapeutic effect and sustained improvement. Conclusion: Yashtimadhu Ksheerapaka Seka proved more effective than artificial tear drops in relieving symptoms and enhancing tear film parameters in Shushkakshipaka, confirming its clinical relevance and therapeutic superiority.